CHOROIDAL MELANOMA IN PHAKOMATOSIS PIGMENTOVASCULARIS WITH KLIPPEL–TRENAUNAY SYNDROME. Issue 11 (November 2018) - Shields, Carol L.; Di Nicola, Maura; Pellegrini, Marco; Shields, Jerry A.
Abstract : Purpose: To describe the relationship of choroidal melanoma with phakomatosis pigmentovascularis in patients with Klippel–Trenaunay syndrome. Methods: Retrospective review of 5 patients. Results: In all 5 cases, the patient was white and the cutaneous port-wine stain was congenital. The port-wine stain involved the chin (n = 1), jawline (n = 2), lower cheek (n = 1), thorax (n = 5), abdomen (n = 4), upper (n = 4), and lower (n = 3) limb(s). The ocular melanocytosis involved the sclera (n = 5), iris (n = 2) and choroid (n = 4). At diagnosis of choroidal melanoma, mean patient age was 57 years (median 61, range 17–83 years). The melanoma demonstrated mean basal diameter of 11.6 mm (median 12, range 5–16 mm) and mean thickness of 5.7 mm (median 6.1, range 2–9), revealing intrinsic tumor pigment and subretinal fluid in all cases. Melanoma management included plaque radiotherapy (n = 3), thermotherapy (n = 1), or enucleation (n = 1). At mean follow-up of 4 years, one patient demonstrated melanoma-related metastasis with death. Conclusion: Phakomatosis pigmentovascularis represents coexistence of Klippel–Trenaunay syndrome (or Sturge–Weber syndrome) and oculo(dermal) melanocytosis, promoting risk for life-threatening uveal melanoma. The authors suggest that all patients with Klippel–Trenaunay syndrome be evaluated for phakomatosis pigmentovascularis and affected patients have dilated fundus examination once or twice a year. Abstract : Five patients with choroidal melanoma demonstrated background phakomatosis pigmentovascularis with Klippel–Trenaunay syndrome, manifesting cutaneous port-wine stain of thorax/abdomen/limb(s) and oculo(dermal) melanocytosis. This syndrome can promote malignant uveal melanoma and requires long-term monitoring.